THE URGENCY OF PROTECTING CHILDREN BORN FROM WOMEN WHO HAD CEASED HER MARRIAGE DUE TO LI’AN *) - Rachmadi Usman; Diana Rahmawati (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2018)
A husband is given the right to deny the child born by his wife as his child, while his wife denies the accusation. If a husband accuses his wife of adultery, but does not complete the evidence by presenting 4 witnesses and his wife refutes the accusation, then they can take the oath of li’an. The child born of the oath of li’an is a child who called as mula’nah or an adulterous child or a child born out ofmarriage. As a result of the legal li’an child, this adulterous child does not have nasab, marriage guardian, inheritance and a living with the man who caused his birth. In order for the li’an child not to be abandoned by his biological father, a biological father should be appointed to take responsibility for fulfilling the life needs of the li’an child concerned. The government has the authority to determinethe punishment of ta’zir to the adulterous man by obliging him to fulfill the life needs of theli’an child, even obliging him to give part of the assets after he dies through obligatory wasiat. This is done in order to fulfill the sense of justice and the interests of children and human rights of a child.